Measurement uncertainty evaluation for yaw error reduction - Harnnarong, Sh; Chinchusak, Wanchai; Numsomran, Arjin; Hormchoey, Pisit; Tipsuwanporn, Vittaya (My University, 2019)
The previous research compared the yaw measurement error between a rotary encoder and a couple of single beam laser (CSL) module, that those result emphasized only repeatability of yaw measurement error. In order to complete correspondingly with the metrological algorithm. This research presents the measurement uncertainty evaluation of yaw measurement error with the CSL module that based on the guide to the expression of uncertainty in measurement. The measurement uncertainty of the CSL module calibration is 12.30 arcsec.
Keywords: A couple of single beam laser; Calibration; CSL module; Measurement uncertainty; Yaw measurement error